"Beauty Unadorned": Dressing Children in Late Nineteenth-Century Ontario - Bates, Christina (Material Culture Review, 1985)
Like all manifestations of culture, the way in which children are clothed reflects the social attitudes of the time. The concern for proper practices of dressing children in the late nineteenth century was part of a larger concern for their mental and moral development. This paper discusses the prevalent attitudes to children in nineteenth-century Ontario, and the influence those attitudes had on children’s dress In particular, the issues in children’s health care affecting the way children were clothed and the attempts at sex and age definition through children’s dress are examined. Résumé Comme toutes les manifestations de la culture, la façon d’habiller les enfants reflète les attitudes sociales d’une époque. L’attention accordée a l habillement des enfants à la fin du XIXe siècle s’inscrivait dans un souci plus général de leur développement mental et de leur éducation morale. Le present document traite des attitudes dominantes à l’égard des enfants en Ontario au XIXe siècle, ainsi que de leurs répercussions sur le vêtement de l’enfant. On y étudie en particulier les questions relatives à l’hygiène des enfants, qui avait une incidence sur leur habillement, et les tentatives de définition du sexe et de l’âge d’un enfant par le vêtement.